Complexation of uranyl (UO2)2+ with bidentate ligands: XRD, spectroscopic, computational, and biological studies. - Abeer A Sharfalddin (Public Library of Science (PLoS), 2021)
Three new uranyl complexes [(UO2)(OAc)2(CMZ)], [(UO2)(OAc)2(MP)] and [(UO2)(OAc)2(SCZ)] were synthesized and characterized by elemental analysis, FT-IR, UV-Vis spectroscopy, powder XRD analysis, and molar conductivity. The IR analysis confirmed binding to the metal ion by the sulfur and ethoxy oxygen atoms in the carbimazole (CMZ) ligand, while in the 6-mercaptopurine (MP) ligand, the sulfur and the N7 nitrogen atom of a purine coordinated binding to the metal ion. The third ligand showed a 1:1 molar ratio and bound via sulfonamide oxygen and the nitrogen of the pyrimidine ring. Analysis of the synthesized complexes also showed that acetate groups had monodentate binding to the (UO22+). Density Functional Theory (DFT) calculations at the B3LYP level showed similar structures to the experimental results. Theoretical quantum parameters predicted the reactivity of the complexes in the order, [(UO2)(OAc)2(SCZ)] > [(UO2)(OAc)2(MP)]> [(UO2)(OAc)2(CMZ)]. DNA binding studies revealed that [(UO2)(OAc)2(SCZ)] and [(UO2)(OAc)2(CMZ)] have the highest binding constant (Kb) among the uranyl complexes. Additionally, strong binding of the MP and CMZ metal complexes to human serum albumin (HSA) were observed by both absorbance and fluorescence approaches. The antibacterial activity of the complexes was also evaluated against four bacterial strains: two gram-negative; Escherichia coli and Klebsiella pneumonia, and two gram-positive; Staphylococcus aureus and Streptococcus mutans. [(UO2)(OAc)2(MP)] had the greatest antibacterial activity against Klebsiella pneumonia, the gram-positive bacteria, with even higher activity than the standard antibiotic. In vitro cytotoxicity tests were also performed against three human cancer lines, and revealed the most cytotoxic complexes to be [(UO2)(OAc)2(SCZ)], which showed moderate activity against a colon cancer cell line. Thus, uranyl addition enhances the antibacterial and anticancer properties of the free ligands.